De san Jorge o el arte del dragoneo - Castro Cuadra, Antonio (Escritura e Imagen, 2007)
The story of St George staged by The Golden Legend of Jac. de Voragine designs an architecture built on four pillars called by the author of the article “law of the father”, “law of de son”, “law of the spirit” and “law of the dragon”. Each law articulates and built the whole in a different way, but their borders are easy to cross. The first appear as three images of the justice detected and understood from different perspectives which are very human, linear and reproductive. The fourth seems to work an take place on the fringe of the human, but it contaminates any point of view with its strange circular tenacity. The dragon, which inaugurates the story and dies so soon, draw it, however, in the interstice that unites and separates the outside, like a kind of untiring architect with no proper name: it dies in a story and returns to life in another, to die again. The dragon, hidden protagonist, spins in its plot as many stories as attempts of reconstruction of the justice, which sooner or later is destroyed or out of joint without remedy. Neither human, nor inhuman, nor divine, the dragoneo shows itself to de living image of the writing, a virtually poetic justice in fieri.